Simultaneous and independent capture of multiple Rayleigh dielectric nanospheres with sine-modulated Gaussian beams - Jingjing Su (Nature Portfolio, 2021)
Abstract This study investigates the propagation properties and radiation forces on Rayleigh dielectric particles produced by novel sine-modulated Gaussian beams (SMGBs) because of the unique focusing properties of four independent light intensity distribution centers and possessing many deep potential wells in the output plane of the target laser. The described beams can concurrently capture and manipulate multiple Rayleigh dielectric spheres with high refractive indices without disturbing each other at the focus plane. Spheres with a low refractive index can be guided or confined in the focus but cannot be stably trapped in this single beam trap. Simulation results demonstrate that the focused SMGBs can be used to trap particle in different planes by increasing the sine-modulate coefficient g. The conditions for effective and stable capture of high-index particles and the threshold of detectable radius are determined at the end of this study.